Biological Evaluation of Protein Meals for Making Nutrient Dense Food Bar - Salim-ur-Rahman; Tarar, Omer Mukhtar; Zahoor, Tahir; Jamil, Khalid; Jamil, Aamer (Pakistan Journal of Nutrition, 2009)
The study was undertaken for biological evaluation of protein meals, differing in raw or processed chickpea (Cicer arietinum L.) and vetch (Lathyrus sativus L.) flour for nutritionally rich food bar making. The indigenous food processing technologies such as controlled and natural fermentation and germination were utilized to improve the protein quality of legumes. The resultant flours were thereafter blended with other protein sources to produce balanced protein meal. The protein quality of these diets was assessed by implying in-vivo rat assays. The values for relative protein efficiency ratio (RPER) and relative net protein ratio (RNPR) in close proximity to each other for processed meals are an indicator of good protein quality of these meals. It could be concluded that food bars with good protein quality can be produced by using meals carrying processed vetch or chickpea.